Renewable energy disclosure in South African listed companies’ corporate reports: An impression management analysis - Schaller, Jessica (University of the Witwatersrand, Johannesburg, 2023)
The emphasis on renewable energy is especially relevant in a South African context. The poor electricity stability has resulted in many businesses incorporating renewable energy into their business model and subsequent disclosures. The disclosures provided by companies are intended to address stakeholders’ information needs regarding the sustainability of a company. The disclosure may, however, contain elements of impression management to reduce agency costs. The report investigates the informativeness of renewable energy disclosures, questioning whether companies adopt impression management strategies by manipulating the disclosures provided in their reports. A content analysis was performed on the disclosures by 60 listed companies. Analysis was performed using descriptive and multivariate statistical analysis to assess the extent of impression management depending on the type of industry, market capitalisation and corporate report used. It was found that companies engage in impression management when disclosing the transition. The findings support that there were mainly similarities noted across industries and market capitalisation in terms of the techniques used, with some differences in terms of the impression management methods used. There were, however, significant differences noted in the overall level of impression management within different industries, market capitalisations and corporate reports. This evidence has relevant implications for both accounting scholars and practitioners since it questions the role of voluntary disclosures and the intended purpose of the disclosures in different reporting media
A research report submitted in partial fulfillment of the requirements for the degree of a Master of Commerce in Accountancy, University of the Witwatersrand, Johannesburg, 2023
Keywords: Renewable energy; Impression management; Legitimacy; Corporate reporting; UCTD; SDG-7: Affordable and clean energy